Identification of Volatile Compounds and Insecticidal Activity of Essential Oils from Origanum compactum Benth. and Rosmarinus officinalis L. against Callosobruchus maculatus (Fab.) - Asmae Baghouz; Yamna Bouchelta; Imane Es-safi; Mohammed Bourhia; El Moussaoui Abdelfattah; Abdullah A. Alarfaj; Abdurahman Hajinur Hirad; Hiba-Allah Nafidi; Raja Guemmouh (Journal of Chemistry)
This work was undertaken to investigate the volatile compounds and insecticidal activity of essential oils (EOs) from Origanum compactum Benth. and Rosmarinus officinalis L. against the crop pest Callosobruchus maculatus (Fab.). Essential oils of Origanum compactum (EOC) and Rosmarinus officinalis L. (EOR) were extracted by use of hydrodistillation, and their volatile compounds were profiled by gas chromatography-mass spectrometry (GC-MS). The insecticidal activity of extracted EOC and EOR was evaluated against C. maculatus. GC-MS analysis revealed that carvacrol (70.88%) and 1,8-cineole (62.35%) were the major constituents of EOC and EOR, respectively. EOC exhibited a potent insecticidal activity with calculated LC50 values of 6.77 and 3.57 μL/L air, 24 and 48 h posttreatment, respectively. Comparable LC50 values were obtained for EOR recording 6.25 and 3.82 μL/L, 48 h posttreatment. The effects of fumigation by the tested EOs on fertility (egg hatching) and the emergence of adult C. maculatus were also investigated. Notably, EOC completely abolished egg fertility judged by the abrogation of emergence of adults, regardless of the tested dose. By contrast, EOR completely inhibited the fertility and the emergence of C. maculatus adults at the dose of 16 μL/10 g. The outcome of the present study highlights the utility of the EOs from O. compactum Benth. and R. officinalis L. as natural sources of effective and ecofriendly pest-control agents.